Optimizing Avian Fertility: Caffeine Modulation of Sperm Motility in Red Junglefowl - Sarkar, Shishir; Kamruzzaman, Md.; Osti, Komal Laxmi; Salma, Ummay; Miah, Abdul Gaffar (International Journal of Applied Sciences and Biotechnology, 2025)
The Red Junglefowl (RJF; Gallus gallus) represents the wild ancestor of domesticated chickens yet its numbers experience reduction because of habitat destruction together with hunting practices and mixed gene flow. The improvement of reproductive biotechnology is an essential requirement for conservation initiatives. The study tested how caffeine impacts sperm motility together with kinematic parameters in RJF semen through CASA. Semen samples were collected from 20 mature RJF males then diluted using increasing caffeine levels (1, 2, 3 and 4 mg/ml) while maintaining a control group with 0 mg/ml of extender. The study determined sperm total motility, progressive motility, curvilinear velocity (VCL), straight-line velocity (VSL), average path velocity (VAP) at 0, 30 and 60 minutes. The sperm motility increased significantly when caffeine was added at 2 mg/ml concentration because total and progressive motility reached maximum levels (P<0.05) at 30 minutes. The specific values for VCL, VSL and VAP reached at the best levels with this level (2 mg/ml). The application of 4 mg/ml caffeine led to decreased sperm movement and raised mortality rates yet revealing harmful effects. These results demonstrate how proper concentrations of caffeine function as performance-enhancing agents that efficiently boost sperm motility in RJF. The appropriate levels of caffeine becomes essential because it displays harmful effects against sperm viability. It is necessary to conduct additional investigations about the sustained impact of caffeine on sperm capabilities alongside its role in semen preservation through freezing methods. The study contributes significant knowledge about using caffeine for research in avian reproductive biotechnology. Int. J. Appl. Sci. Biotechnol. Vol 13(1): 38-45.